Caracterização de programas de intervenção com crianças e/ou adolescentes - Bolsoni-Silva, Alessandra Turini [UNESP] (2010)
The objective was to present a descriptive analysis of interventions to prevent and/or reduce children's and/or adolescents' problem behaviors. The study reviewed 192 abstracts from journal articles published between the 1986 and June 2006, available on the following databases: Index-Psi/Periódicos, Lilacs, PsycInfo, Scielo and Medline. Categories of analysis focused on bibliography, method, and studies' results. Data-analysis showed that most of the studies focused on groups and families, and samples with more than 30 participants. Study designs were experimental and quasi-experimental, combining observation and self report or just self report for data collection. Result analysis suggests that the intervention programs contributed specially for reducing behavior problems, and improving parental practices. Discussion evaluates contributions of the study and gaps in knowledge.